Potential role of serum hypoxia-inducible factor 1alpha as a biomarker of delayed cerebral ischemia and poor clinical outcome after human aneurysmal subarachnoid hemorrhage: A prospective, longitudinal, multicenter, and observational study - Cai, Ye-Yan; Zhuang, Yao-Kun; Wang, Wen-Jian; Jiang, Feng; Hu, Jie-Miao; Zhang, Xiao-Le; Zhang, Li-Xin; Lou, Xiao-Hui (Frontiers in Neurology, 2022)
Objective: Hypoxia-inducible factor 1alpha (HIF-1α) functions as a crucial transcriptional mediator in hypoxic and ischemic brain response. We endeavored to assess the prognostic significance of serum HIF-1α in human aneurysmal subarachnoid hemorrhage (aSAH). Methods: In this prospective, longitudinal, multicenter, observational study of 257 aSAH patients and 100 healthy controls, serum HIF-1α levels were quantified. Univariate analyses, followed by multivariate analyses, were performed to discern the relationship between serum HIF-1α levels and severity, delayed cerebral ischemia (DCI) plus post-stroke 6-month poor outcome (extended Glasgow outcome scale (GOSE) scores of 1-4). Predictive efficiency was determined under receiver operating characteristic (ROC) curve. Results: There were significantly increased serum HIF-lα levels after aSAH, in comparison to controls (median, 288.0 pg/ml versus 102.6 pg/ml; P<0.001). Serum HIF-lα levels were independently correlated with Hunt-Hess scores (β, 78.376; 95% confidence interval (CI), 56.446-100.305; P=0.001) and modified Fisher scores (β, 52.037; 95% CI, 23.461-80.614; P=0.002). Serum HIF-lα levels displayed significant efficiency for discriminating DCI risk (area under ROC curve (AUC), 0.751; 95% CI, 0.687-0.815; P<0.001) and poor outcome (AUC, 0.791; 95% CI, 0.736-0.846; P<0.001). Using the Youden method, serum HIF-1α levels > 229.3 pg/ml predicted the development of DCI with 92.3% sensitivity and 48.4% specificity; and serum HIF-1α levels > 384.0 pg/ml differentiated the risk of a poor prognosis with 71.4% sensitivity and 81.1% specificity. Serum HIF-1α levels > 229.3 pg/ml were independently predictive of DCI (odds ratio (OR), 3.061; 95% CI, 1.045-8.965; P=0.041) and serum HIF-1α levels > 384.0 pg/ml was independently associated with a poor outcome (OR, 2.907; 95% CI, 1.403-6.024; P=0.004). The DCI predictive ability of their combination was significantly superior to those of Hunt-Hess scores (AUC, 0.800; 95% CI, 0.745-0.855; P=0.039) and modified Fisher scores (AUC, 0.784; 95% CI, 0.726-0.843; P=0.004). And, the prognostic predictive ability of their combination substantially exceeded those of Hunt-Hess scores (AUC, 0.839; 95% CI, 0.791-0.886; P<0.001) and modified Fisher scores (AUC, 0.844; 95% CI, 0.799-0.890; P<0.001). Conclusions: Elevated serum HIF-lα levels after aSAH, in independent correlation with stroke severity, were independently associated with DCI and poor outcome, substantializing serum HIF-lα as a potential prognostic biomarker of aSAH.